2017
DOI: 10.11648/j.sjph.20170503.23
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Timely Response to Health Care Seeking for Diarrheal Episodes Among Children Under Five by Caregivers in Rural Uganda

Abstract: Timely response to health care seeking for diarrhoea episodes has a high potential to reduce child mortality rates.This study aimed to investigate the factors influencing timely response to health care seeking for diarrheal episode among children under five by caregivers. A cross-sectional research design that involved qualitative and quantitative research methods was conducted among 1,780 systematically selected households. Multiple logistic regressions were carried out to identify the factors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…The observations of our study indicated that health care utilization for diarrhea illness was in agreement with a study conducted in the rural parts of South Africa (50%) [31]. On the other hand, our finding is lower than previous studies conducted in the rural parts of Niger (70.4%) and Uganda (76%) [17, 19]. The finding of the study also showed that health care utilization for fever illness was higher than a study conducted in Nigeria [32].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observations of our study indicated that health care utilization for diarrhea illness was in agreement with a study conducted in the rural parts of South Africa (50%) [31]. On the other hand, our finding is lower than previous studies conducted in the rural parts of Niger (70.4%) and Uganda (76%) [17, 19]. The finding of the study also showed that health care utilization for fever illness was higher than a study conducted in Nigeria [32].…”
Section: Discussionsupporting
confidence: 91%
“…In the rural parts of Kenya, health care was sought for only one-third of the children with both fever and diarrhea illnesses [16], and 82% of the caregivers used health centers for treating diarrhea in rural Uganda [17]. Nearly three-quarters (74.3%) of the children with fever, 77.3% of the children with Acute Respiratory Infection (ARI) and 23.0% of the children with diarrhea were initially treated at a health facilities in rural Tanzania [18].…”
Section: Introductionmentioning
confidence: 99%
“…Mothers/caregivers of female children were more likely to delay than mothers/caregivers of male children. The finding is consistent with previous research in Woliso, Ethiopia, India and rural Uganda [18,24,28] and study reported by Global DHS on care seeking and access to health care for childhood illness reported that males were more likely to seek care early [25]. In addition, the existing literature in different developing countries regarding health care seeking for females display that female disadvantage in health care seeking [29].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with results from other studies. 7,15 Being far away from health facilities imposes a challenge on mothers/ caregivers because it enforces them to travel long distances which could result in tiredness, being off from a job, and may incur additional costs for transportation.…”
Section: Discussionmentioning
confidence: 99%
“…13 Delayed care seeking could affect child health significantly and can lead to complications that make medical care less effective or, in some cases, useless. 14 The majority of caregivers of children with diarrheal diseases in developing counties did not seek healthcare timely 7,11,15 or not sought at all. [16][17][18][19][20] For instance, a study from India reported that about 33.8% of children with diarrheal diseases were taken to a health facility one day after the onset of the illness.…”
Section: Introductionmentioning
confidence: 99%